THE CONTENT OF IMPROVING METHODOLOGICAL TRAINING OF FUTURE PRIMARY CLASS TEACHERS - MJ Saidova (Western European Studies, 2024)
In this article, an opinion is expressed about the methodical training of the future primary school teacher, views related to his professional activity, problems of professional and personal training formation, the system of their elimination, and the main directions of improving the cognitive activity of primary school teachers.
Keywords: Future primary school teacher; methodological training; quality of education